(untitled) (Journal of Economics, Law and Society, 2024)
We are pleased to present the second issue of the Journal of Economics, Law, and Society (JELS). This issue builds on the foundations laid in our inaugural publication, continuing to explore the critical intersections between economics, law, and societal dynamics. Our aim remains to foster scholarly discourse that bridges diverse disciplines, addressing contemporary challenges with innovative, multidisciplinary approaches. The second issue features five diverse and thought-provoking articles that contribute to the advancement of knowledge in Islamic finance, economic sustainability, and the historical evolution of financial systems. Each article underscores the journal’s commitment to high-quality research and its role as a platform for intellectual exchange.